Sustainability Assessment of Remanufactured Computers - Fatimah, Y.; Biswas, Wahidul (2016)
The accelerating growth of communication and information technologies (CITs) worldwide has caused the exponential growth of end-of-life (EoL) computers and e-waste. Remanufacturing of EoL computers has thus potential to enhance resource conservation and prevent natural resources degradation, which obviously have social, economic and environmental benefits. Fatimah et al (2013) framework has been applied to determine remanufacturing strategies to achieve the sustainability of remanufactured computers. The results showed that remanufactured computers could be technically, environmentally, economically and socially feasible if there is an adequate supply of quality cores, involvement of high skilled workers, incorporation of standardization process, and the use of advanced machines tools.